Great Tits Learn Odors and Colors Equally Well, and Show No Predisposition for Herbivore-Induced Plant Volatiles - Rubene, Diana; Urhan, Utku; Ninkovic, Velemir; Brodin, Anders (Frontiers in Ecology and Evolution, 2022)
Ability to efficiently localize productive foraging habitat is crucial for nesting success of insectivorous birds. Some bird species can use olfaction to identify caterpillar-infested trees by detection of herbivore induced plant volatiles (HIPVs), but these cues probably need to be learned. So far, we know very little about the process of olfactory learning in birds, whether insectivorous species have a predisposition for detecting and learning HIPVs, due to the high ecological significance of these odors, and how olfaction is integrated with vision in making foraging decisions. In a standardized setup, we tested whether 35 wild-caught great tits (Parus major) show any preference for widely abundant HIPVs compared to neutral (non-induced) plant odors, how fast they learn to associate olfactory, visual and multimodal foraging cues with food, and whether the olfactory preferences and learning speed were influenced by bird sex or habitat (urban or rural). We also tested how fast birds switch to a new cue of the same modality. Great tits showed no initial preference for HIPVs compared to neutral odors, and they learned all olfactory cues at a similar pace, except for methyl salicylate (MeSA), which they learned more slowly. We also found no differences in learning speeds between visual, olfactory and multimodal foraging cues, but birds learned the second cue they were offered faster than the first one. Bird sex or habitat had no effect on learning speed or olfactory preference, but urban birds tended to learn visual cues more slowly. We conclude that insectivorous birds utilize olfactory and visual cues with similar efficiency in foraging, and that they probably don`t have any special predisposition towards the tested HIPVs. These results confirm that great tits are flexible foragers with good learning abilities.